牙尖覆盖厚度对全瓷高嵌体修复前磨牙应力分布影响的三维有限元分析 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2019)
OBJECTIVE: To investigate the influence of cuspal-coverage thickness on the stress distribution of all-ceramic onlay-restored premolars by using 3D finite element (FE) analysis and to provide references for the design of all-ceramic onlays for clinical application. METHODS: 3D FE models of all-ceramic onlays with three cuspal-coverage thicknesses (2, 3, and 4 mm) of endodontically treated maxillary premolar were constructed based on micro-CT images. Stress distributions in the onlay, adhesive resin cement layer, and dentin of models were analyzed under vertical load (600 N) and oblique load (200 N). RESULTS: When the cuspal-coverage thickness increased, the peak maximum principal stress value decreased inside the onlay but increased in the margin of the adhesive resin cement layer. In addition, stress concentration areas increased in the coronal residual dentin on the palatal side under oblique load. CONCLUSION: An increase in the cuspal-coverage thickness of all-ceramic onlays may reduce the risk of rupture of the restoration but may deteriorate the restoration and cause palatal dentin fracture.